Determinants associated with carpal tunnel syndrome complaints - Andi We Tenri Batari Toja Kamri; Nasruddin Syam; Arman Arman (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Carpal Tunnel Syndrome (CTS) is one of the most common problems in the upper extremities caused by the narrowing of the carpal tunnel, which results in pressure on the median nerve. Increased pressure in the carpal tunnel causes compression and damage to the median nerve. Objective: determinants associated with carpal tunnel syndrome . Methods: quantitative research with a cross-sectional research design. The sampling technique in this study used a total sampling technique in which the entire population is equal to the number of samples, namely 36 people. Data obtained by using a questionnaire. The analytical method used was univariate and bivariate analysis using the chi-square test. Result: showed that there was a relationship between length of work and carpal tunnel syndrome (p-value = 0.0190. There is a relationship between age and complaints of carpal tunnel syndrome (p-value = 0.032. There is no relationship between personal protective equipment and complaints of carpal tunnel syndrome (p-value = 0.759). There is no relationship between repetitive movements and carpal tunnel syndrome (p-value = 0.787. Conclusion: It was concluded that there is a relationship between length of service and carpal tunnel syndrome complaints, there is a relationship between age and carpal tunnel syndrome complaints and there is no relationship between body mass index and carpal tunnel syndrome complaints . In this study, researchers suggest to companies to pay more attention to employees who have a long working period so as not to do excessive work and for employees to take advantage of adequate rest time to minimize the occurrence of complaints of Carpal Tunnel Syndrome (CTS).